El expresionismo: representación pictórica del desnudo masculino tomando como referente la obra de Egon Schiele, aplicando técnicas contemporáneas - Yaguana Quito, Alex Paúl (2021)
The present investigative work called: "Expressionism: pictorial representation of the male nude taking as a reference the work of Egon Schiele, applying contemporary techniques", proposes the study of the male nude in the artistic field and its analysis within expressionist painting. The main reference for the process of making the work is the artistic work of the Viennese artist Egon Schiele. To achieve the objectives, different research methods are used according to each of the phases, among them are: the deductive and inductive method, which allowed to deepen and analyze the different topics through the collection of information. With the empirical method through observation, experimentation and artistic references, the plastic proposal is structured in its pre-production-production and post-production phases. The pictorial work was made based on the experimentation of materials and artistic techniques from the male nude represented through the expressionist style, exploring the conceptual and poetic possibilities by the artist, resulting in a reality framed in the context of representing a personal experience from the psychological point of view, rooted in anguish and depression for human existence itself